log(x-1)-log(x+1)-log(8)=-2

Simple and best practice solution for log(x-1)-log(x+1)-log(8)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for log(x-1)-log(x+1)-log(8)=-2 equation:


Simplifying
log(x + -1) + -1log(x + 1) + -1log(8) = -2

Reorder the terms:
glo(-1 + x) + -1log(x + 1) + -1log(8) = -2
(-1 * glo + x * glo) + -1log(x + 1) + -1log(8) = -2
(-1glo + glox) + -1log(x + 1) + -1log(8) = -2

Reorder the terms:
-1glo + glox + -1glo(1 + x) + -1log(8) = -2
-1glo + glox + (1 * -1glo + x * -1glo) + -1log(8) = -2
-1glo + glox + (-1glo + -1glox) + -1log(8) = -2

Reorder the terms for easier multiplication:
-1glo + glox + -1glo + -1glox + -1 * 8glo = -2

Multiply -1 * 8
-1glo + glox + -1glo + -1glox + -8glo = -2

Reorder the terms:
-1glo + -1glo + -8glo + glox + -1glox = -2

Combine like terms: -1glo + -1glo = -2glo
-2glo + -8glo + glox + -1glox = -2

Combine like terms: -2glo + -8glo = -10glo
-10glo + glox + -1glox = -2

Combine like terms: glox + -1glox = 0
-10glo + 0 = -2
-10glo = -2

Solving
-10glo = -2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '-10lo'.
g = 0.2l-1o-1

Simplifying
g = 0.2l-1o-1

See similar equations:

| 2x-7y+z=-5 | | x^3+4x^2+60x-17=0 | | log(x-1)-2*log(x+1)-log(8)=-2 | | x+2x+2=2 | | -3=57+(n+1)-4 | | -3m(m-10)=0 | | 5x-7=3(x+3) | | -3x=40000 | | 5x-11=2(x+14) | | 40-8x=32 | | -3a-16b-38a+24b= | | 5x-8/2=2x | | 2*6x-52=9x-196 | | x=42-10+4 | | s*4-39=9 | | 60x=0 | | 1*6x-52=9x-196 | | 10*6x-52=9x-196 | | 4x-34=14 | | x-x/2-x/6=40000 | | sinx=sin(5^/9 | | sinx=sin(5pie/9 | | X*x+1=702 | | X^3+5x^2+6x+1=0 | | Sinx=sin(3pi/5 | | sin=sin(5pi/9) | | ln(15x-20)-ln(5)=3 | | Cosx=cos-11pi/9 | | x^2+mx-2m=0 | | 57x-10y=m | | Tan64=x/15 | | 0.2x+x=5000 |

Equations solver categories